Invasive meningococcal disease in South-Eastern European countries: Do we need to revise vaccination strategies? - Georgina Tzanakaki; Hana Cabrnochová; Snežana Delić; Anca Draganescu; Anna Hilfanova; Beáta Onozó; Marko Pokorn; Anna Skoczyńska; Goran Tešović (Human Vaccines & Immunotherapeutics)
Invasive meningococcal disease (IMD) is an acute life-threatening infection caused by the gram-negative bacterium, Neisseria meningitidis. Globally, there are approximately half a million cases of IMD each year, with incidence varying across geographical regions. Vaccination has proven to be successful against IMD, as part of controlling outbreaks, and when incorporated into national immunization programs. The South-Eastern Europe Meningococcal Advocacy Group (including representatives from Croatia, the Czech Republic, Greece, Hungary, Poland, Romania, Serbia, Slovenia and Ukraine) was formed in order to discuss the potential challenges of IMD faced in the region. The incidence of IMD across Europe has been relatively low over the past decade; of the countries that came together for the South-Eastern Meningococcal Advocacy Group, the notification rates were lower than the European average for some country. The age distribution of IMD cases was highest in infants and children, and most countries also had a further peak in adolescents and young adults. Across the nine included countries between 2010 and 2020, the largest contributors to IMD were serogroups B and C; however, each individual country had distinct patterns for serogroup distribution. Along with the variations in epidemiology of IMD between the included countries, vaccination policies also differ.